ATP2B1 expression identifies human hematopoietic stem cells with superior repopulation and self-renewal - Angelica Varesi; Murtaza S. Nagree; Isabella Di Biasio; Andy G. X. Zeng; Sayyam Shah; Michael Zhang; Hyerin Kim; Alex Murison; Rohail Badami; Olga Gan; Liqing Jin; Jessica McLeod; et al. (Proceedings of the National Academy of Sciences, 2026)
Long-term hematopoietic stem cells (LT-HSC) maintain lifelong hematopoiesis while preserving the stem cell compartment through self-renewal. The human LT-HSC compartment is molecularly and functionally heterogeneous and also varies across ontogeny. Dissecting the molecular basis for this variation is impeded by the paucity of immunophenotypic markers to resolve LT-HSC heterogeneity. Here, we identified ATPase plasma membrane calcium transporting 1 (ATP2B1/PMCA1) as a cell surface marker that is heterogeneously expressed by CD49f + LT-HSC from fetal to adult hematopoiesis. ATP2B1 immunophenotypic expression stratified human CD49f + LT-HSC from fetal liver, neonatal cord blood, and adult mobilized peripheral blood sources into functionally distinct subpopulations in single-cell (sc) clonogenic assays. CD49f + ATP2B1 + LT-HSC exhibited superior long-term repopulation and self-renewal capacities in vivo compared to CD49f + ATP2B1 – LT-HSC. Molecular profiling by scMultiome and immunofluorescence microscopy point to enrichment of an HSC self-renewal program that includes the TFEB–endolysosomal axis in CD49f + ATP2B1 + LT-HSC. Our study provides a framework to dissect the heterogeneous molecular programs in LT-HSC.